Forecasting Inflation in Indonesia - Ramakrishnan, Uma (IMF Working Papers; Working Paper, 2002)
A reliable inflation-forecasting model is central for a sound monetary policy framework. In this paper, we study the domestic and international transmission effects on inflation in Indonesia and analyze the possible leading indicators of inflation. We identify the exchange rate, foreign inflation, and monetary growth as the main variables with a significant predictive power for inflation in Indonesia.